Stan cywilny osób homoseksualnych a zasada niedyskryminacji w orzecznictwie TSUE na tle odpowiedzi na pytanie prejudycjalne w sprawie c-267/12 – Frédéric Hay przeciw Credit Agricole mutuel de charente-maritime et des deux-sèvres: [The civil status of the homosexuals and the non-discrimination rule in the case-law of the court of justice of the European Union Against on? A background of the case no c-267/12 – Frédéric Hay v. Credit Agricole mutuel de charente-maritime et des deux-sè] (Studia Prawnicze / The Legal Studies, 2015)
W dniu 12.12.2013 r. TSUE odpowiedział na pytanie prejudycjalne w sprawie C-267/12 – Frédéric Hay przeciwko Crédit agricole mutuel de Cha-rente-Maritime et des Deux-Sèvres.Orzeczenie podtrzymuje i rozwija linię orzeczniczą Trybunału dotyczącą zasady niedyskryminacji w sprawach pracowniczych związanych ze stanem cywilnym zainteresowanych osób homoseksualnych. Rozstrzygnięcie pokazuje oddziaływanie prawa europejskiego na prawo krajowe w kwestiach pozostających na styku kompetencji państw członkowskich i prawa unijnego, jako że kwestie stanu cywilnego nie weszły do katalogu wyłącznych kompetencji UE na podstawie prawa pierwotnego. Jego analiza skłania do ukazania i skomentowania założeń przyjętego przez Trybunał kierunku orzekania co do materii, która pozostaje w różnym zakresie i w różny sposób uregulowana w poszczególnych państwach członkowskich. The text shows impact of the EU law on the internal legal order in question sat the edge of competences of the Members States, as matters of civil status stay beyond the exclusive competences of the EU. The ECJ develops previous case-law concerning relation between the non-discrimination rule and sex-orientation in the labor matters. In the light of the Council Directive 2000/78/EC establishing a general framework for equal treatment in employment and occupation, the CJEU treated the French PACS concluded by a homosexual couple at the same way as a marriage in spite of the fact that the French legislation had highly differentiated both statuses at the moment when the facts of the case took place. The provisions of “the bank collective agreement, […] under which an employee who concludes a civil solidarity pact with a person of the same sex is not allowed to obtain the same benefits, such as days of special leave and a salary bonus, as those granted to employees on the occasion of their marriage, where the national rules of the Member State concerned do not allow persons of the same sex to marry” create a direct discrimination in the light of the Art.2(2)(a) of Directive2000/78/EC.